Notes on neophytes I. Silene noctiflora L. (Caryophyllaceae) registered for Mexico - Vibrans, Heike (Instituto de Ecología, A.C., 1995)
Silene noctiflora L. (Caryophyllaceae) is recorded for the first time from Mexico. It is naturalized in maize fields near Orizaba, Veracruz.